2000
DOI: 10.1098/rspb.2000.0977
|View full text |Cite
|
Sign up to set email alerts
|

Non–random fitness variation in two populations of Darwin's finches

Abstract: Darwinian ¢tness of an individual is measured by the number of recruits it contributes to the next generation. We studied variation in ¢tness among members of three cohorts of two species of Darwin's ¢nches living on the Gala¨pagos island of Daphne Major: the medium ground ¢nch (Geospiza fortis) and cactus ¢nch (Geospiza scandens). Individuals of both species live for up to 16 years. Variation in ¢tness was neither random nor heritable. Non-randomness arises as a result of a few individuals living for an excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 31 publications
5
46
0
Order By: Relevance
“…On the other hand, our results do agree with previous studies conducted on laboratory and wild rodents which find no evidence of V A in metabolic traits (Lacy and Lynch 1979;Lynch et al 1988;Dohm et al 1996Dohm et al , 2001Nespolo et al 2003a). Concerning morphological traits, many studies have reported high values of h 2 (Boonstra and Boag 1987;Roff 1997;Endler 2000;Grant and Grant 2000;Hoffman 2000;Kruuk et al 2000;Brooks and Endler 2001), which is in agreement with a previous study on P. darwini that also found high h 2 for tarsus length (Nespolo et al 2003a). Conversely we found h 2 not different from zero for the dry masses of central organs, with the exception of the liver (h 2 ϭ 0.73).…”
supporting
confidence: 79%
“…On the other hand, our results do agree with previous studies conducted on laboratory and wild rodents which find no evidence of V A in metabolic traits (Lacy and Lynch 1979;Lynch et al 1988;Dohm et al 1996Dohm et al , 2001Nespolo et al 2003a). Concerning morphological traits, many studies have reported high values of h 2 (Boonstra and Boag 1987;Roff 1997;Endler 2000;Grant and Grant 2000;Hoffman 2000;Kruuk et al 2000;Brooks and Endler 2001), which is in agreement with a previous study on P. darwini that also found high h 2 for tarsus length (Nespolo et al 2003a). Conversely we found h 2 not different from zero for the dry masses of central organs, with the exception of the liver (h 2 ϭ 0.73).…”
supporting
confidence: 79%
“…lifetime reproductive success) would require multigeneration pedigrees, which could not be obtained. Regardless, previous work on G. fortis has confirmed that 'the most important determinant of fitness is the ability of an individual to survive to breed in many years' (Grant & Grant 2000). One of the reasons is that periodic droughts (and other factors) can eliminate reproduction and cause very high adult mortality in a given year.…”
Section: Methodsmentioning
confidence: 99%
“…At the outset, an ancestral species colonized multiple islands characterized by ecological differences, such as different seed size distributions. Resulting divergent selection among allopatric populations then caused their adaptive divergence, most notably in beak and body dimensions (Bowman 1961;Abbott et al 1977;Schluter & Grant 1984;Grant & Grant 2000, 2008. Next, further dispersal among the islands brought some allopatric forms back into secondary contact (Grant 1986;Petren et al 2005;), where several outcomes were possible.…”
Section: Introductionmentioning
confidence: 99%
“…He became almost completely silent and then paired not with a G. magnirostris female but with a G. fortis female. In this case, pair formation was based on morphology and not on song (Grant & Grant 2008 (Grant & Grant 2000). With beaks of generally intermediate size hybrids can feed on small soft seeds but are unable to crack the large and hard seeds of T. cistoides, even though they occasionally try.…”
Section: Hybridizationmentioning
confidence: 99%